Anti-human CD138 monoclonal antibodies and their bispecific formats: generation and characterization. (3rd May 2016) - Chen, Dan; Zou, Jianxuan; Zong, Yunhui; Meng, Huimin; An, Gangli; Yang, Lin
Abstract: Syndecan-1 (CD138), a heparan sulfate proteoglycan, acts as a co-receptor for growth factors and chemokines and is a molecular marker associated with the epithelial–mesenchymal transition during development and carcinogenesis. In this study, we generated two specific mouse anti-human CD138 monoclonal antibodies (mAbs, clone ID: 480CT5.4.3, 587CT7.3.6.5) using hybridoma technology and identified their immunological characteristics. After hybridoma sequencing, the single-chain variable fragments (ScFvs) cloned from two hybridoma cells were combined with anti-CD3 OKT-3 ScFv to generate two recombinant bispecific antibodies (h-STL002, m-STL002) against CD138 and CD3 molecules, respectively. The bispecific antibodies were able to specifically target CD138 + multiple myeloma (MM) cells and CD3 + T cells, and showed the potent cytotoxicity against MM RPMI-8226 cell line through T cell activation. However, these bispecific antibodies without T cells did not cause toxic side effect on MM cells. Overall, the two hybridoma clones and their bispecific formats have great potential to promote diagnosis and immunotherapy of plasma cell malignancy.